An enhanced mitochondrial function through glutamine metabolism in plasmablast differentiation in systemic lupus erythematosus. (3rd November 2021) - Sumikawa, Maiko Hajime; Iwata, Shigeru; Zhang, Mingzeng; Miyata, Hiroko; Ueno, Masanobu; Todoroki, Yasuyuki; Nagayasu, Atsushi; Kanda, Ryuichiro; Sonomoto, Koshiro; Torimoto, Keiichi; Lee, Seunghyun; Nakayamada, Shingo; et al.
Abstract: Objective: To evaluate the dysfunction of B-cell metabolism and its involvement in SLE pathology. Methods: We assessed the expression of metabolic markers of B cells in the peripheral blood of healthy controls (HCs) and SLE patients by using flow cytometry. In vitro, peripheral B cells were isolated from HCs and SLE patients to investigate the metabolic regulation mechanisms involved in their differentiation. Results: The expression level of DiOc6 (mitochondrial membrane hyperpolarization) was higher in B cells from SLE patients than in HCs, and correlated to the percentage of plasmablasts in CD19 + cells and with SLEDAI, a disease activity score. Stimulation of CD19 + cells with the Toll-like receptor 9 (TLR9) ligand CpG and IFN-α enhanced glycolysis, oxidative phosphorylation (OXPHOS), DiOc6 expression, and plasmablast differentiation in vitro . In the absence of glutamine, both glycolysis and OXPHOS were reduced, and plasmablast differentiation was suppressed, whereas there was no change in the absence of glucose. As glutamine is an important nutrient for protein synthesis, we further investigated the effect of the glutaminase inhibitor BPTES, which inhibits glutamine degradation, on metabolic regulation. BPTES reduced DiOc6 expression, OXPHOS, reactive oxygen species (ROS) production, adenosine triphosphate (ATP) production, plasmablast differentiation without affecting glycolysis. Metformin inhibited CpG- and IFN-α-induced glutamine uptake, mitochondrial functions and suppressed plasmablast differentiation. Conclusions: Mitochondrial dysfunction in B cells is associated with plasmablast differentiation and disease activity in SLE. Enhanced mitochondrial functions mediated by glutamine metabolism are important for plasmablast differentiation, which may be a potential therapeutic target for SLE.